Changing Trend in Colorectal Carcinoma in Central India - Bandhate, Kamal; Diwan, Ashok Kumar; Mahobia, Vijay; Khan, Subeera (Asian Journal of Medical Research, 2021)
According to some data it has been seen that colorectal carcinoma has been showing some change in its trend of occurrence amongst young individuals. This is a retrospective study done on patients who were diagnosed with colorectal carcinoma between 2017 and 2020. The data was acquired from the Departmental record of the Department of Radiation Oncology, GMCH, Nagpur. A total of 330 patients were included in the final analysis.